Geogebra As A 21st Century Learning Tool: A Systematic Literature Review - Salsanabila, Maulina Fakhrunnisa; Lestari, Dian Endang; Sari, Dela Yulanda (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Learning in the 21st century requires the use of media in learning which results in new desires and interests, increases motivation and stimulation in learning, and even has a psychological effect on students. Technology-based learning media can make learning more interesting, because the use of appropriate media can help convey material abstractly, so that students can more easily understand the material. The existence of technology in learning mathematics helps students in understanding mathematical concepts. One form of math learning media is GeoGebra. This study aims to analyze the distribution of education levels, materials, and 21st century skills that are most often used in the application of the GeoGebra application as a 21st Century Mathematics learning media. The research method used was systematic literature review. The research subjects were 33 journal articles obtained from the Scopus, Google Scholars, ScienceDirect, Springer, ResearchGate, OJS (Open Journal System), and Eric databases in the last 7 years. The results showed that the study of 21st century geogebra increased in 2020 and the peak occurred in 2022 with the research method used dominated by quasi-experiments. In addition, the junior high school education level, geometry transformation material and analytic geometry of the field, as well as creative thinking skills become the most dominating and widely conducted research.